Modified magnetic wood powder, functional wood-plastic composite material and preparation method of modified magnetic wood powder and functional wood-plastic composite material
Through the preparation of modified magnetic wood powder, the problems of micro-nano plastic particles removal and nano-magnetic particles reuse in water are solved, efficient adsorption and magnetic separation are achieved, secondary pollution is avoided, and the utilization efficiency of materials is improved.
Patent Information
- Application Number
- CN202411725878.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The prior art is difficult to effectively remove small-sized micro-nano plastic particles in water, and nanomagnetic particles are prone to agglomeration during water treatment, affecting adsorption efficiency, and the material is difficult to reuse after adsorption.
Modified magnetic wood powder is used, which improves the dispersion and adsorption efficiency in water by forming magnetic materials and hydrophobic long-chain alkyl grafting on the surface of the wood powder, and realizes the recycling and reuse of the material through an external magnetic field.
Modified magnetic wood powder has good dispersion in water, can efficiently adsorb micro-nano plastic particles, and can avoid secondary pollution through magnetic field separation, while achieving the reuse of nanomagnetic particles and improving the utilization efficiency of materials.
Smart Images

Figure CN119592093A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sewage purification and restoration and waste recycling, and in particular to a modified magnetic wood powder, a functional wood-plastic composite material prepared by the modified magnetic wood powder for absorbing micro-nano plastics in a solution, and a preparation method thereof. Background Art
[0002] In recent years, the degree of plastic pollution in the environment has shown a continuous upward trend. Plastics accumulate in the environment, causing pollution to water sources, soil, atmosphere and other environments on which humans depend for survival. Micro-nano plastics refer to plastics with a particle size range of 1nm to 5μm. Due to their small size, micro-nano plastic particles can enter the body through water, food or air, reach organs and tissues, cause physiological changes, structural damage and functional disorders, and pose a potential threat to human health. Therefore, it is very urgent to use appropriate methods to separate micro-nano plastic particles from their existence medium, especially the water environment.
[0003] There are many ways for the traditional water treatment industry to deal with micro-nano plastic particles, such as membrane bioreactor (MBR), rapid sand rate method, dissolved air flotation (DAF), etc. These methods have high removal efficiency for microplastics with a particle size greater than 20μm, but these traditional methods are not suitable for removing small-sized micro-nano plastics. In addition, there are flocculation, filtration, microalgae adsorption and other methods. The flocculation method separates micro-nano plastic particles from water by co-precipitation, and its processing cost is low, but it is easy to cause secondary pollution. The filtration method uses a filter medium with high porosity and small pore size, and the removal efficiency is relatively high, but it still cannot completely intercept small-sized micro-nano plastics, and the filter medium will have clogging problems after long-term use. The microalgae adsorption method does not use chemical agents, but it is difficult to recover the adsorbed micro-nano plastics, which will have toxic effects on microalgae.
[0004] In response to the above problems, nanoscale magnetic particles, due to their own charged characteristics, can adsorb charged micro-nano plastic particles through charge action after reasonably adjusting their potential, and are ideal materials for treating micro-nano plastic particles in water. Among them, magnetic iron oxide nanoparticles can adsorb nanoscale micro-nano plastic particles such as polystyrene (PS), polymethyl methacrylate (PMMA), polyethylene (PE), and then remove them from the water by applying an external magnetic field. However, nanoscale magnetic particle adsorption materials are prone to agglomeration during water treatment, which affects their dispersion in water, and further leads to a decrease in their adsorption capacity for micro-nano plastic particles. Secondly, the desorption efficiency of the magnetic particle material after adsorbing micro-nano plastics is low and cannot be further used, resulting in insufficient material utilization efficiency.
[0005] Therefore, how to improve the dispersibility of nanomagnetic particles in water to enhance their adsorption efficiency on micro-nano plastic particles and reuse the nanomagnetic particle materials after adsorbing micro-nano plastics is an urgent problem to be solved. Summary of the invention
[0006] In order to solve the problems existing in the above-mentioned background technology, the present invention provides a modified magnetic wood powder and a preparation process thereof. The modified magnetic wood powder has good dispersibility in the solution, can effectively adsorb micro-nano plastic particles in the solution, and can be removed from the solution using a magnet. In addition, the present invention also provides a functional wood-plastic composite material and a preparation method thereof, which realizes the recycling and reuse of nano-magnetic particle materials after adsorbing micro-nano plastic particles. The modified magnetic wood powder that adsorbs micro-nano plastic particles in the solution is prepared by hot pressing to obtain a functional wood-plastic composite material with excellent physical and mechanical properties, magnetism, electromagnetic wave absorption and flame retardancy.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] The first aspect of the present invention provides a method for preparing modified magnetic wood powder, comprising the following steps:
[0009] S1. Preparation of magnetic wood powder:
[0010] The magnetic wood powder is prepared by reacting wood powder of 50-150 mesh with ferric chloride hexahydrate, ferrous chloride tetrahydrate and ammonia water;
[0011] S2. Preparation of modified magnetic wood powder:
[0012] Hexadecyltrimethoxysilane is dissolved in methanol, and then magnetic wood powder is added thereto, and then washed after ultrasonic reaction and dried to obtain modified magnetic wood powder.
[0013] Using the above technical solution:
[0014] First, the surface of wood powder contains a large number of hydroxyl groups, which can react with the metal ions (Fe 3+ and Fe 2+ ) complexes to adsorb metal ions onto the surface of wood powder. After adding ammonia, it reacts with Fe 3+ and Fe 2+The ions react to form water-insoluble ferric hydroxide (Fe(OH)3) and ferrous hydroxide (Fe(OH)2) precipitates, which are deposited on the surface of the wood powder and eventually form magnetic materials on the surface of the wood powder after subsequent transformation. Then, the magnetic wood powder is modified by treating it with hexadecyltrimethoxysilane (HDTMS). The hydrophobic long-chain alkyl of HDTMS is grafted onto the surface of the wood powder, which improves the dispersion effect and dispersion stability of the magnetic wood powder in water and reduces agglomeration. It can effectively adsorb the micro-nano plastic particles in the solution containing them, thereby more thoroughly adsorbing the micro-nano plastic particles in the water. At the same time, its magnetic properties are conducive to separating them from the water using an external magnetic field after adsorption, and will not cause secondary pollution to the water environment.
[0015] Furthermore, the step S2 is specifically as follows: dissolving hexadecyltrimethoxysilane in methanol to obtain a mixed solution with a volume concentration of 1 to 8%, adding magnetic wood powder thereto, ultrasonically treating for 3 to 5 minutes, removing the modified magnetic wood powder from the solution under the action of a magnet, washing it with methanol, and drying it in an oven to prepare modified magnetic wood powder.
[0016] Furthermore, in step S1, the wood powder is pretreated, specifically: the wood powder is placed in an ethanol solution with a volume concentration of ≥20%, stirred at 50-80°C for 1-3h, the treated wood powder is separated and washed with deionized water, and then the wood powder is dried to obtain pretreated wood powder.
[0017] The wood powder is pretreated with ethanol to change its surface properties and become an excellent carrier of magnetic particles.
[0018] Furthermore, in the step S1, the preparation process of the magnetic wood powder is specifically as follows: preparing a mixed solution of ferric chloride hexahydrate with a mass concentration of 10-30% and ferrous chloride tetrahydrate with a mass concentration of 5-10%, adding wood powder to the mixed solution, and vacuum impregnating for 1-5 hours; after impregnation, adding an ammonia solution with an equal volume to the mixed solution, stirring evenly and continuing vacuum impregnation for 1-5 hours; after the impregnation is complete, removing the magnetic wood powder from the solution under the action of a magnet to prepare magnetic wood powder loaded with ferrosoferric oxide particles.
[0019] The second aspect of the present invention provides a modified magnetic wood powder, which is prepared by the above preparation method.
[0020] After experimental testing, the maximum adsorption rate of the modified magnetic wood powder for micro-nano plastic particles in water was 2571 mg / g.
[0021] The third aspect of the present invention provides a method for preparing a functional wood-plastic composite material, comprising the following steps:
[0022] (1) Adsorption of micro-nano plastic particles in water:
[0023] The modified magnetic wood powder prepared above is added to a solution containing micro-nano plastic particles for stirring and adsorption, and then the modified magnetic wood powder adsorbed with the micro-nano plastic particles is removed from the solution by a magnet, and then dried;
[0024] (2) Preparation of wood-plastic composite materials:
[0025] The modified magnetic wood powder adsorbed with micro-nano plastic particles after drying is added into a hot pressing mold, and a functional wood-plastic composite material is obtained through hot pressing molding.
[0026] Using the above technical solution:
[0027] In the present invention, modified magnetic wood powder adsorbed with micro-nano plastic particles is prepared into a functional wood-plastic composite material through hot pressing. Compared with ordinary wood-plastic composite materials, the plastic components of the functional wood-plastic composite material come from the water body, which can not only achieve the removal of micro-nano plastic pollutants in sewage, but also achieve the recycling and reuse of waste resources (waste wood powder and micro-nano plastic particles in sewage). Compared with ordinary wood-plastic composite materials, the prepared functional wood-plastic composite material not only has better strength, but also has more special functions, such as magnetism, flame retardancy and electromagnetic wave absorption function, and can be widely used in the field of engineering construction.
[0028] Furthermore, in the step (2), the hot pressing molding process is specifically as follows: hot pressing time is 30 to 60 minutes, pressure is 5 to 20 MPa, and temperature is 120 to 220°C.
[0029] Furthermore, the step (1) is specifically as follows: placing the prepared modified magnetic wood powder in a solution containing micro-nano plastic particles, stirring for more than 20 minutes at 20-60° C. and a rotation speed of 300-500 rpm / min, and after the stirring is completed, using a magnet to remove the modified magnetic wood powder adsorbed with the micro-nano plastic particles from the solution, and then drying it.
[0030] Furthermore, the micro-nano plastic particles contained in the solution are thermoplastic plastics, the size of the micro-nano plastic particles is 50nm-5μm, and the pH value of the solution containing the micro-nano plastic particles is 2-9.
[0031] A fourth aspect of the present invention provides a functional wood-plastic composite material, which is prepared by the above preparation method.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) Selection of raw materials Wood powder is a common processing residue in the wood industry. It is not only low-carbon and environmentally friendly, easy to obtain, and low in cost, but also has a large specific surface area and is easy to process. The wood powder is pretreated with ethanol to change its surface properties, making it an excellent carrier of magnetic particles.
[0034] (2) The wood powder loaded with magnetic particles on the surface is modified by using hexadecyltrimethoxysilane (HDTMS) to treat the magnetic wood powder. The hydrophobic long-chain alkyl of HDTMS is grafted onto the surface of the wood powder, which improves the dispersion effect and dispersion stability of the magnetic wood powder in water and reduces the agglomeration phenomenon. It can effectively adsorb the magnetic wood powder in a solution containing micro-nano plastic particles, thereby more thoroughly adsorbing the micro-nano plastic particles in the water. At the same time, its magnetic properties are conducive to separating it from the water using an external magnetic field after adsorption, and will not cause secondary pollution to the water environment.
[0035] (3) The prepared modified magnetic wood powder has excellent adsorption effect on a variety of plastic particle pollutants in the water environment, including those of different sizes, micrometers and nanometers, and different types, such as polyethylene (PE), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), polymethyl methacrylate (PMMA), polycarbonate (PC) and other common plastics; at the same time, it is also applicable in different acid and alkali environments and has universal applicability, with its maximum adsorption efficiency reaching 2571 mg / g.
[0036] (4) The present invention then prepares a functional wood-plastic composite material by hot pressing the modified magnetic wood powder adsorbed with micro-nano plastic particles. Compared with ordinary wood-plastic composite materials, the plastic components of the functional wood-plastic composite material come from the water body, which can not only remove micro-nano plastic pollutants in sewage, but also realize the recycling and reuse of waste resources (waste wood powder and micro-nano plastic particles in sewage).
[0037] (5) Thanks to the loaded magnetic particles, the functional wood-plastic composites prepared by using modified magnetic wood powder adsorbed with micro-nano plastic particles not only have better strength than ordinary wood-plastic composites, but also have more special functions, such as magnetism, flame retardancy and electromagnetic wave absorption, and can be widely used in the field of engineering construction. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0039] Figure 1 It is a schematic diagram of the process of preparing a functional wood-plastic composite material from magnetic wood powder that absorbs micro-nano plastic particles in water in the present invention;
[0040] Figure 2 This is a scanning electron microscope image of the modified magnetic wood powder prepared in Example 1;
[0041] Figure 3 The graphs showing the variation of the adsorption amount of 5 μm and 400 nm PS and PMMA plastic particles by the modified magnetic wood powder prepared in Examples 1 to 4 as a function of adsorption time;
[0042] Figure 4 The physical picture and magnetization curve of the functional wood-plastic composite material obtained by hot-pressing the modified magnetic wood powder prepared in Example 2 after absorbing PS plastic particles and being attracted by a magnet;
[0043] Figure 5 The scanning electron microscope image and Fe element distribution map of the functional wood-plastic composite material obtained by hot pressing the modified magnetic wood powder prepared in Example 2 after absorbing PS plastic particles. DETAILED DESCRIPTION
[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Example 1
[0046] A method for preparing a functional wood-plastic composite material by using magnetic wood powder adsorbing micro-nano plastic particles in water, such as Figure 1 As shown, the following steps are included:
[0047] (1) Using a powder sifter to sieve out 60-mesh wood powder, the wood powder is placed in a 65% ethanol solution, stirred at 70°C for 2 hours, and then the wood powder is separated by a suction filtration device and washed with deionized water. The wood powder is then moved into an oven and dried until it is absolutely dry to obtain pretreated wood powder.
[0048] (2) A mixed solution of ferric chloride hexahydrate with a mass concentration of 15% and ferrous chloride tetrahydrate with a mass concentration of 7% is prepared, and then the pretreated wood powder is added and vacuum impregnation is performed for 3 hours; after impregnation, an ammonia solution with an equal volume to the mixed solution is added, and the mixture is stirred evenly and vacuum impregnation is continued for 3 hours; after the impregnation is complete, the magnetic wood powder is removed from the solution under the action of a magnet to prepare a magnetic wood powder loaded with ferrosoferric oxide particles.
[0049] (3) Hexadecyltrimethoxysilane is dissolved in methanol to form a mixed solution with a volume concentration of 5%, magnetic wood powder is added thereto, and after ultrasonic treatment for 5 minutes, the modified magnetic wood powder is removed from the solution under the action of a magnet, washed with methanol, and then dried in an oven to absolute dryness to prepare modified magnetic wood powder.
[0050] (4) The prepared modified magnetic wood powder was placed in water containing 5 μm PS plastic particles, and stirred at a temperature of 25°C and a speed of 300 rpm / min for more than 80 minutes. After the stirring was completed, the modified magnetic wood powder adsorbed with the micro-nano plastic particles was removed from the solution under the action of a magnet, and then dried in a drying oven at 70°C.
[0051] (5) The dried modified magnetic wood powder adsorbed with micro-nano plastic particles is placed in a hot pressing mold for hot pressing molding, wherein the hot pressing time is 40 min, the pressure is 10 MPa, the temperature is 180° C., and the thickness of the board is controlled to be 5 mm using a thickness gauge, and finally a functional wood-plastic composite material is obtained.
[0052] Example 2
[0053] Compared with Example 1, this embodiment is different in that:
[0054] In step (4), the prepared modified magnetic wood powder is placed in water containing 400 nm PS plastic particles.
[0055] The rest are the same as in Example 1.
[0056] Example 3
[0057] Compared with Example 1, this embodiment is different in that:
[0058] In step (4), the prepared modified magnetic wood powder is placed in water containing 5 μm PMMA plastic particles.
[0059] The rest are the same as in Example 1.
[0060] Example 4
[0061] Compared with Example 1, this embodiment is different in that:
[0062] In step (4), the prepared modified magnetic wood powder is placed in water containing 400 nm PMMA plastic particles.
[0063] The rest are the same as in Example 1.
[0064] Comparative Example 1
[0065] The untreated wood powder was directly mixed with 5 μm PS plastic particles and loaded into a hot pressing mold for hot pressing molding. The ratio of wood powder to plastic was kept the same as the calculated value of plastic adsorption in Example 1. During the hot pressing molding process, the hot pressing time was 40 min, the pressure was 10 MPa, the temperature was 180° C., and the thickness of the board was controlled to be 5 mm by a thickness gauge, and finally an ordinary wood-plastic composite material was obtained.
[0066] Comparative Example 2
[0067] The untreated wood powder was directly mixed with 400nmPS plastic particles and loaded into a hot pressing mold for hot pressing molding. The ratio of wood powder to plastic was kept the same as the plastic adsorption calculated value in Example 1. During the hot pressing molding process, the hot pressing time was 40min, the pressure was 10MPa, the temperature was 180°C, and the thickness of the board was controlled to be 5mm by a thickness gauge, and finally an ordinary wood-plastic composite material was obtained.
[0068] Comparative Example 3
[0069] The untreated wood powder was directly mixed with 5 μm PMMA plastic particles and loaded into a hot pressing mold for hot pressing molding. The ratio of wood powder to plastic was kept the same as the plastic adsorption calculated value in Example 1. During the hot pressing molding process, the hot pressing time was 40 min, the pressure was 10 MPa, the temperature was 180° C., and the thickness of the board was controlled to be 5 mm by a thickness gauge, and finally an ordinary wood-plastic composite material was obtained.
[0070] Comparative Example 4
[0071] The untreated wood powder was directly mixed with 400nm PMMA plastic particles and loaded into a hot pressing mold for hot pressing molding. The ratio of wood powder to plastic was kept the same as the plastic adsorption calculated value in Example 1. During the hot pressing molding process, the hot pressing time was 40min, the pressure was 10MPa, the temperature was 180°C, and the thickness of the board was controlled to be 5mm by a thickness gauge, and finally an ordinary wood-plastic composite material was obtained.
[0072] Application Example 1
[0073] The modified magnetic wood powder prepared in Example 1 was analyzed by scanning electron microscope. Figure 2 ,pass Figure 2 It can be seen from the scanning electron microscopy results that a layer of ferrosoferric oxide particles is loaded on the surface of the wood powder, indicating that the modified magnetic wood powder is successfully prepared according to the steps of the present invention.
[0074] Subsequently, the modified magnetic wood powder prepared in Examples 1-4 was tested for adsorption performance. The test results are as follows: Figure 3 And as shown in Table 1.
[0075] Table 1 Adsorption of modified magnetic wood powder on PS and PMMA plastics
[0076] serial number Plastic Type and Size Adsorption capacity (mg / g) Example 1 5μmPS 2571±37 Example 2 400nmPS 186.4±5.3 Example 3 5μmPMMA 2544±47 Example 4 400nmPMMA 103.7±12.2
[0077] Depend on Figure 3As shown in Table 1, the modified magnetic wood powder prepared in Examples 1-4 has good adsorption capacity for PS and PMMA in water, and the modified magnetic wood powder has a better adsorption capacity for micron-sized plastic particles. In addition, the adsorption capacity of the modified magnetic wood powder for plastic particles in Examples 1-4 increases with the extension of the adsorption time, and reaches adsorption saturation at about 80 minutes.
[0078] Application Example 2
[0079] The functional wood-plastic composite materials prepared in Examples 1 and 3 and the ordinary wood-plastic composite materials prepared in Comparative Examples 1 and 3 were subjected to mechanical and water absorption tests, and the test results are shown in Table 2. A mechanical testing machine was used to perform bending and tensile strength tests on all samples to be tested. The samples to be tested were placed in a drying oven and dried to absolute dryness, and their weight and thickness values were recorded; then the samples were placed in a water tank containing deionized water for soaking, and their weight and thickness were measured after soaking for 20 days, and the weight change rate and water absorption thickness expansion rate of the samples before and after water absorption were calculated.
[0080] Table 2 Mechanical strength and water absorption of functional wood-plastic composites and ordinary wood-plastic composites
[0081]
[0082] It can be seen from Table 2 that the functional wood-plastic composite materials prepared in Examples 1 and 3 have significantly increased flexural strength and tensile strength compared to the ordinary wood-plastic composite materials prepared in Comparative Examples 1 and 3. In particular, the flexural strength of Example 1 is increased by about 4.4 times compared to Comparative Example 1, which indicates that the functional wood-plastic composite material prepared by the present invention has better mechanical properties. In addition, the prepared functional wood-plastic composite material exhibits lower water absorption and water absorption thickness expansion than ordinary wood-plastic composite materials, which also indicates that it has better dimensional stability. These physical and mechanical performance improvements indicate that the functional wood-plastic composite material prepared by adsorbing micro-nano plastics can be applied to engineering materials.
[0083] Application Example 3
[0084] The magnetic properties, flame retardancy and wave absorption properties of the functional wood-plastic composite materials prepared in Examples 2 and 4 and the ordinary wood-plastic composite materials prepared in Comparative Examples 2 and 4 were tested. The magnetic properties of the samples were tested using a vibrating sample magnetometer, the combustion performance was tested using a cone calorimeter according to ISO5660-1 standard, and the wave absorption performance of the samples was tested using a microwave network vector analyzer.
[0085] Table 3 Flame retardant properties of functional wood-plastic composites and ordinary wood-plastic composites
[0086]
[0087] Depend on Figure 4and Figure 5 It can be seen that the functional wood-plastic composite material prepared in Example 2 can be easily attracted by a magnet without falling off; and the magnetic saturation intensity of Example 2 reaches 10.6emu / g, while Comparative Example 2 has no magnetic intensity and does not have magnetism. The magnetism of Example 2 is mainly due to the presence of ferroferric oxide particles in its components, and obvious Fe elements can be observed from the results of its element scanning. For this reason, the ferroferric oxide particles contained in the functional wood-plastic composite material prepared in Example 2 give it excellent absorption performance, and its maximum electromagnetic wave absorption value in the range of 2-18GHz reaches -22.4dB.
[0088] From the flame retardant test results in Table 3, it can be seen that the functional wood-plastic composite materials prepared in Example 2 and Example 4 have lower heat release rates and total heat release than the ordinary wood-plastic composite materials in Comparative Examples 2 and 4. Among them, the peak heat release rate and total heat release of Example 4 are 34% and 26.8% lower than those of Comparative Example 4, respectively; and in terms of smoke release, Example 4 is 85.7% lower than that of Comparative Example 4. It can be seen that the present invention can not only efficiently adsorb micro-nano plastics in water by preparing modified magnetic wood powder, but also the functional wood-plastic composite material prepared by the wood powder after adsorption has excellent physical and mechanical properties and special functions of magnetism, wave absorption and flame retardancy.
[0089] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing modified magnetic wood powder, characterized in that: The steps include: S1. Preparation of magnetic wood powder: The magnetic wood powder is prepared by reacting wood powder of 50-150 mesh with ferric chloride hexahydrate, ferrous chloride tetrahydrate and ammonia water; S2. Preparation of modified magnetic wood powder: Hexadecyltrimethoxysilane is dissolved in methanol, and then magnetic wood powder is added thereto, and then washed after ultrasonic reaction and dried to obtain modified magnetic wood powder.
2. The method for preparing modified magnetic wood powder according to claim 1, characterized in that: The step S2 specifically comprises: dissolving hexadecyltrimethoxysilane in methanol to obtain a mixed solution with a volume concentration of 1 to 8%, adding magnetic wood powder thereto, ultrasonically treating for 3 to 5 minutes, removing the modified magnetic wood powder from the solution under the action of a magnet, washing it with methanol, and drying it in an oven to prepare modified magnetic wood powder.
3. The method for preparing modified magnetic wood powder according to claim 1, characterized in that: In the step S1, the wood powder is pretreated, specifically: the wood powder is placed in an ethanol solution with a volume concentration of ≥20%, stirred at 50-80°C for 1-3h, the treated wood powder is separated and washed with deionized water, and then the wood powder is dried to obtain pretreated wood powder.
4. The method for preparing the modified magnetic wood powder according to claim 1 or 3, characterized in that: In the step S1, the preparation process of the magnetic wood powder is specifically as follows: a mixed solution of ferric chloride hexahydrate with a mass concentration of 10-30% and ferrous chloride tetrahydrate with a mass concentration of 5-10% is prepared, wood powder is added to the mixed solution, and vacuum impregnation is performed for 1-5 hours; after impregnation, an ammonia solution with an equal volume to the mixed solution is added, and vacuum impregnation is continued for 1-5 hours after stirring evenly; after the impregnation is complete, the magnetic wood powder is removed from the solution under the action of a magnet to prepare magnetic wood powder loaded with ferrosoferric oxide particles.
5. A modified magnetic wood powder, characterized in that: The invention discloses a method for preparing the present invention according to any one of claims 1 to 4.
6. A method for preparing a functional wood-plastic composite material, characterized in that: The steps include: (1) Adsorption of micro-nano plastic particles in water: The modified magnetic wood powder of claim 5 is added to a solution containing micro-nano plastic particles for stirring and adsorption, and then the modified magnetic wood powder adsorbed with the micro-nano plastic particles is removed from the solution by a magnet, and then dried; (2) Preparation of wood-plastic composite materials: The modified magnetic wood powder adsorbed with micro-nano plastic particles after drying is added into a hot pressing mold, and a functional wood-plastic composite material is obtained through hot pressing molding.
7. The method for preparing the functional wood-plastic composite material according to claim 6, characterized in that: In the step (2), the hot pressing process is specifically as follows: hot pressing time is 30 to 60 minutes, pressure is 5 to 20 MPa, and temperature is 120 to 220°C.
8. The method for preparing the functional wood-plastic composite material according to claim 6, characterized in that: The step (1) specifically comprises: placing the prepared modified magnetic wood powder in a solution containing micro-nano plastic particles, stirring for more than 20 minutes at 20-60° C. and a rotation speed of 300-500 rpm / min, and after the stirring is completed, removing the modified magnetic wood powder adsorbed with the micro-nano plastic particles from the solution with a magnet, and then drying the solution.
9. The method for preparing the functional wood-plastic composite material according to claim 6 or 8, characterized in that: The micro-nano plastic particles contained in the solution are thermoplastic plastics, the size of the micro-nano plastic particles is 50nm-5μm, and the pH value of the solution containing the micro-nano plastic particles is 2-9.
10. A functional wood-plastic composite material, characterized in that: It is prepared by the preparation method according to any one of claims 6 to 9.
Citation Information
Patent Citations
Magnetic wood-plastic composite material and preparation method thereof
CN103937279A
Preparation method for magnetic recoverable super-hydrophobic super-oleophylic adsorbent by taking wood flour as raw material
CN105964231A
Magnet-wood composite material
WO2017029325A1